Tourism development in Japan : themes, issues and challenges - Sharpley, Richard, 1956-; Kato, Kumi (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This significant and timely volume focuses on the unique trajectory of tourism development in Japan, which has been characterised by an historical emphasis on promoting both domestic and international tourism to Japanese tourists, followed by the more recent policy of competing aggressively in the international incoming tourist market. Initial chapters present an overview of past and present tourism including policy and research perspectives. Thematic perspectives on tourism and specific contexts and places in which tourism occurs are then examined. Strains of Japanese tourism such as sport, surf, forest, mountain, urban, tea, pilgrimage, and even whaling heritage tourism are among those analysed. The book also explores tourism's role in confronting difficult pasts and presents, and the challenges facing the development of tourism in contemporary Japan. A short post-script outlines some of the challenges and possible future directions tourism in Japan may take in light of the COVID-19 crisis. Written by a team of well-known editors and contributors including academics from Japan, this will be of great interest to upper-students and researchers and academics in Development Studies, Cultural Studies, Geography and Tourism"--
Introduction : tourism in Japan -- from the past to the present / Richard Sharpley & Kumi Kato -- Tourism research on Japan : overview of major trends : Japanese and English-language materials / Yumiko Horita & Kumi Kato -- Urban development and tourism in Japanese cities / Yumiko Horita -- Transition of forest tourism policies in Japanese national forest management / Yumi Oura -- A systematic review of sport tourism research in Japan / Eiji Ito and Tom Hinch -- Mobilising stoke : a genealogy of surf tourism development in Miyazaki, Japan / Adam Doering -- Japan's mountain tourism at a crossroads : insights from the North Japan Alps / Abhik Chakraborty -- International exchange in tea tourism : reconceptualizing Japanese green tourism for sustainable farming communities / Amnaj Khaokhrueamuang -- Pilgrimage tourism in regional communities : the case of Tanabe City and Kumano Kodo / Ricardo Nicolas Progano and Kumi Kato -- Confronting difficult pasts : the case of 'kamikaze' tourism / Richard Sharpley and Kumi Kato -- Whaling heritage and tourism development : 'sliced, diced and boiled down' / Simon Wearne -- Debating sustainability in tourism development : resilience, traditional knowledge and community : a post-disaster perspective / Kumi Kato -- International tourists in Japan : their increasing numbers and vulnerability to natural hazards / Hayato Nagai, Kaede Sano, Brent W. Ritchie and Takashi Yoshino -- The expansion of peer-to-peer accommodation rentals in Japan : issues and challenges / Takahiro Ikeji and Hayato Nagai -- Postscript / Richard Sharpley & Kumi Kato.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Japan; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism